2008
DOI: 10.1108/02652320810894370
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the drivers of internet banking adoption decision

Abstract: PurposeThe paper seeks to compare, through empirical evidence, two widely adopted models (the Technology Acceptance Model (TAM) and the Diffusion of Innovations (DoI) model) to an underutilized one (Perceived Characteristics of the Innovation) in order to examine which is better in predicting consumer adoption of internet banking (IB), while investigating innovation attributes vis‐à‐vis other important predictors of adoption of innovations, such as consumer personal characteristics.Design/methodology/approachT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 67 publications
7
104
1
Order By: Relevance
“…These two values were found to be comparatively lower than the values from the earlier studies measuring influences of different independent variables on the adoption of a given innovation (Ungan, 2004;Gounaris and Koritos, 2008;Li. 2008).…”
Section: Fig 2 Validated Model Illustrating Attributes Influencing contrasting
confidence: 49%
“…These two values were found to be comparatively lower than the values from the earlier studies measuring influences of different independent variables on the adoption of a given innovation (Ungan, 2004;Gounaris and Koritos, 2008;Li. 2008).…”
Section: Fig 2 Validated Model Illustrating Attributes Influencing contrasting
confidence: 49%
“…This idea is supported by Chong, et al, (2010, p. 272), "Given that users do not have face to-face interaction in an internet environment, user friendliness and the ease of use of the web sites will lessen the threat to use internet banking by the customers." Many of the researches supported that there is a positive and upward relationship between the perceived ease of use and the probability of adoption of internet banking (Wang, et al, 2003;Hernandez & Mazzon, 2007;Gounaris & Koritos, 2008). On the other hand, other researches (Pikkarainen et al, 2004;Eriksson et al, 2005) contradicted this result and concluded that the ease of use has no influence on the internet adoption.…”
Section: Independent Variablesmentioning
confidence: 65%
“…By that way, this research also elicits each person aware which advantages they can get more than the traditional bank and how efficiency this service brings about. These findings are consisted with the previous researches of Rao et al [29], Pikkarainen et al [30] and Gounaris and Koritos [31].…”
Section: Premise Of Knowledge Factormentioning
confidence: 86%